The trajectory of immunoglobulins immune response against the different amounts of xenobiotics matches the trajectory of biological changes associated with ageing: A systematic review - Yilkal, Tariku Belay (Journal of Aging Research And Healthcare, 2023)
Background Ageing is a life process in which progressive molecular, cellular, physiological and anatomical changes manifesting in humans and animals including other organisms lead to the decline of biological functions. Immunoglobulins (Igs) are glycoprotein molecules produced by white blood cells mainly B lymphocytes following signal transduction as a result of their interaction with pathogenic microbes or poisonous substances introduced into the body systems. They elicit responses against the side effects of pathogens and poisons in which their response efficiency usually declines as we are ageing. Objective Thus, the similarities between Igs’ immune response against the different amounts of xenobiotics and the biological changes associated with ageing have been systematically assessed using the reports of different study results on humans and animals. Methods First, a literature search was carried out in google, PubMed and google scholar using planned search terms related to the title of this study. Review and original articles were retrieved, downloaded and saved on a computer. And then the effects of different factors i.e. xenobiotics, age, sex and lifestyle-based practices on the levels of serum Igs (IgG, IgA and IgM) in animals and humans have been studied using a systematic review of different literature sources. Finally, the relationship between the findings of various studies has been assessed and judgment on the possible cause of ageing has been made. Results The findings of different research have demonstrated that the signaling efficiency of immunoglobulin M (IgM) has been limited by the amount of test compounds administered to study Balb c mice in the oral route. The response efficiency of IgM immune response against the lower doses of test compounds were high compared to the higher doses of test compounds which was low. The results of different other studies also demonstrated that the decline of serum IgM levels was associated with ageing. The relationship between alcohol consumption and the concentration of serum Igs was also described in the report of different studies. These studies have shown that there was lower level of IgG in the blood serum of alcohol consumers compared to non-consumers. The study has also demonstrated a lower level of serum IgM with higher alcohol consumption and higher serum concentration with moderate beer consumption. Conclusion The trajectory of Igs’ immune response against different amounts of xenobiotics was highly associated with the trajectory of biological changes during ageing. These research findings might be the possible evidence to conclude that ageing is caused by the foodstuffs and non-foodstuffs we usually consume, the lifestyles we usually experience and the way of life we usually live in the environment which gradually defiling the natural processes of the body.
Keywords: Ageing; Balb c mice; immunoglobulins immune response; Genetic information